Penyakit-Penyakit di Bidang Psikiatri yang Harus Dituntaskan di Puskesmas - Sri Idaiani (Jurnal Kebijakan Kesehatan Indonesia, 2016)
ABSTRACTBackground: Since January 1st 2014, Indonesia has imple- mented the national health insurance. Indonesian Doctor Com- petency Standard 2012 and Ministry of Health Regulation No 5 in 2014 about clinical practice guideline of doctor in primary care were applied as reference. The aim of this analysis was to give reccomendation related to psychiatric diseases have to be controlled and completely treated by doctors in primary health careMethods: This article was a study of health policy, literature review followed by verification from several experts and vis- iting to two primary health centers (PHCs) in Jakarta and Bogor on July to September 2014.Results: Four psychiatric diseases have to be controlled and completely treated in PHC are insomnia, dementia, mixed anxi- ety depression disorder, and psychosis. In general, patients visiting in PHC have physical, mental and social problems. It was undifferentiated cases and not fulfills the diagnostic cri- teria if examined by psychiatric interview and cause psychiat- ric cases were very limited reported in PHC.Conclusion and Recommendation: The gap of psychiat- ric cases that were not reported is possibly caused by very strict diagnostic criteria therefore doctor in PHC cannot detect psychiatric disease with low severity. This study suggests the need of special psychiatric diagnostic in PHC considering diagnosis, severity, chronicity, and disability. Keywords: psychiatric diseases, primary health center, clinical practice guideline. ABSTRAKLatar belakang: Sejak tanggal 1 Januari 2014 di Indonesia dilaksanakan Jaminan Kesehatan Nasional (JKN). Sebagai rujukannya diterapkan Standar Kompetensi Dokter Indonesia tahun 2012 dan Permenkes Nomor 5 tahun 2014 tentang Panduan Praktik Klinik dokter di pelayanan primer. Tujuan analisis ini adalah untuk memberikan rekomendasi terhadap penyakit- penyakit dibidang psikiatri yang harus dikuasai dan tuntas ditangani oleh dokter di pelayanan kesehatan primer.Metode: Artikel ini adalah telaah kebijakan kesehatan, kepus- takaan dilanjutkan dengan verifikasi dengan beberapa narasumber dan kunjungan di dua Puskesmas di Jakarta dan Kota Bogor. Dilaksanakan pada bulan Juli sampai September 2014.Hasil: Empat penyakit dibidang psikiatri yang harus dapat dituntaskan di Puskesmas adalah insomnia, demensia, gangguan campuran cemas dan depresi, dan psikosis. Pada umumnya pasien Puskesmas mempunyai banyak gejala fisik, psikologik dan masalah sosial. Bila dilakukan pemeriksaan psikiatri, merupakan kasus-kasus yang tidak terdiferensiasi (undifferentiated) dan tidak memenuhi kriteria diagnostik sehingga kasus gangguan jiwa selalu tidak terlaporkan.Kesimpulan dan Saran: Kesenjangan kasus gangguan jiwa yang tidak terlaporkan di Puskesmas mungkin disebabkan oleh kriteria diagnostik yang sangat ketat sehingga dokter di pelayanan primer tidak mampu mendeteksi gangguan dengan keparahan yang lebih rendah. Hasil telaah ini mengusulkan perlunya kode diagnosis di Puskesmas yang memperhatikan diagnosis, severitas, kronisitas dan disabilitas. Kata kunci: penyakit dibidang psikiatri, Puskesmas, panduan praktik klinik